2003
DOI: 10.1007/s00299-003-0673-y
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in loblolly pine ( Pinus taeda L.): improving culture initiation with abscisic acid and silver nitrate

Abstract: Loblolly pine ( Pinus taeda L.) culture initiation was improved by the addition of abscisic acid (ABA) (3.7 micro M), silver nitrate (20 micro M), and guanosine 3',5'-cyclic monophosphate, 8-bromo-, sodium salt (10 micro M) to the medium and by raising cytokinin levels in the presence of 50 mg/l activated carbon (AC). Basal medium contained modified 1/2-P6 salts, 50 mg/l AC, Cu and Zn added to compensate for adsorption by AC, 1.5% maltose, 2% myo-inositol, 500 mg/l casamino acids, 450 mg/l glutamine, 2 mg/l al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 38 publications
1
26
0
4
Order By: Relevance
“…Zygotic embryos in cotyledonary stage resulted in low induction rates and these cultures did not show embryogenic competence (data not show). The embryogenic induction rates observed in the present work were higher than those observed in other conifer species such as Pinus taeda that presented a mean induction rate of 17.9% (Pullman et al, 2003). The data obtained in the present work confirmed previous results with A. angustifolia (Guerra et al, 2000;Santos et al, 2002 in which the pre-cotyledonary stage of developmental showed enhanced competence for embryogenic induction.…”
Section: Resultssupporting
confidence: 80%
“…Zygotic embryos in cotyledonary stage resulted in low induction rates and these cultures did not show embryogenic competence (data not show). The embryogenic induction rates observed in the present work were higher than those observed in other conifer species such as Pinus taeda that presented a mean induction rate of 17.9% (Pullman et al, 2003). The data obtained in the present work confirmed previous results with A. angustifolia (Guerra et al, 2000;Santos et al, 2002 in which the pre-cotyledonary stage of developmental showed enhanced competence for embryogenic induction.…”
Section: Resultssupporting
confidence: 80%
“…patula para inducir formación de brotes (McKellar et al, 1994). La calidad del embrión somático es menor que el cigótico en cuanto a morfología, peso seco, germinación y estabilidad genética (Pullman, 2003). Sin embargo, aunque se presenten ciertas limitantes, la embriogénesis somática es una técnica exitosa y potencial para la producción de diversas especies forestales (Cheng y Voqui, 1977;Arya, et al, 2000).…”
Section: Methodsunclassified
“…patula to induce shoot formation (McKellar et al, 1994). The quality of somatic embryos is lower than that of zygotic ones in morphology, dry weight, germination and genetic stability (Pullman, 2003). However, although it has certain limitations, somatic embryogenesis is a successful technique with potential for the production of various forest species (Cheng and Voqui 1977;Arya et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos trabalhos têm sido realizados com o cultivo in vitro de espécies do gênero Pinus, como: P. patula (McKELLAR et al, 1994), P. elliottii (BURNS et al, 1991), P. heldreichii (STOJIEIÉ et al, 1999) e P. taeda (LI e HUANG, 1996;PULLMAN et al, 2003). Tais pesquisas são, em seu maior número, ligadas à embriogênese somática, processo mais difícil e trabalhoso, tanto pelos explantes necessários (os quais geralmente necessitam de coleta em estágio imaturo) quanto pela execução laboratorial.…”
Section: Segundo O Instituto De Pesquisas E Estudos Florestaisunclassified